2023
DOI: 10.3390/jcm12237210
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Conventional Operations: Embracing the Era of Contemporary Minimally Invasive Cardiac Surgery

Lilly Ilcheva,
Petar Risteski,
Igor Tudorache
et al.

Abstract: Over the past two decades, minimally invasive cardiac surgery (MICS) has gained a significant place due to the emergence of innovative tools and improvements in surgical techniques, offering comparable efficacy and safety to traditional surgical methods. This review provides an overview of the history of MICS, its current state, and its prospects and highlights its advantages and limitations. Additionally, we highlight the growing trends and potential pathways for the expansion of MICS, underscoring the crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 157 publications
(312 reference statements)
0
2
0
Order By: Relevance
“…With the rapid development of minimally invasive cardiac surgery, an increasing number of patients have benefited from this approach. The current minimally invasive cardiac approaches include S-shaped partial sternotomy, upper J incision, upper T incision, right parasternal incision, inferior segment sternotomy, and incisions between ribs ( 11 - 14 ). As multiple processes are involved in the Bentall procedure, such as AVR, coronary anastomosis, and ascending aorta replacement, upper sternotomy has become the main incision for this procedure ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of minimally invasive cardiac surgery, an increasing number of patients have benefited from this approach. The current minimally invasive cardiac approaches include S-shaped partial sternotomy, upper J incision, upper T incision, right parasternal incision, inferior segment sternotomy, and incisions between ribs ( 11 - 14 ). As multiple processes are involved in the Bentall procedure, such as AVR, coronary anastomosis, and ascending aorta replacement, upper sternotomy has become the main incision for this procedure ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies comparing hybrid lung resections to traditional open thoracotomies have shown shorter hospital stays, reduced postoperative pain, and quicker recovery times. Additionally, hybrid CABG has emerged as a viable alternative for high-risk patients who may not be suitable candidates for traditional CABG alone, offering improved cardiac function and a lower risk of complications [21].…”
Section: Cardiothoracic Surgerymentioning
confidence: 99%